2020
DOI: 10.17759/exppsy.2020130305
|View full text |Cite
|
Sign up to set email alerts
|

Perception of “Live” Facial Expressions

Abstract: The article provides a review of experimental studies of interpersonal perception on the material of static and dynamic facial expressions as a unique source of information about the person’s inner world. The focus is on the patterns of perception of a moving face, included in the processes of communication and joint activities (an alternative to the most commonly studied perception of static images of a person outside of a behavioral context). The review includes four interrelated topics: face statics and dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…Numerous studies in this paradigm -for a review, see (Barabanschikov, Zhegallo, Korolkova, 2016) have shown that the experimental results obtained are not consistent with Ekman's neurocultural theory of emotions. Individual results can vary greatly, and the distinction between images is not always associated with their different categorical assignment.…”
Section: Introductionmentioning
confidence: 78%
“…Numerous studies in this paradigm -for a review, see (Barabanschikov, Zhegallo, Korolkova, 2016) have shown that the experimental results obtained are not consistent with Ekman's neurocultural theory of emotions. Individual results can vary greatly, and the distinction between images is not always associated with their different categorical assignment.…”
Section: Introductionmentioning
confidence: 78%